2013
DOI: 10.1111/php.12065
|View full text |Cite
|
Sign up to set email alerts
|

PDT Dose Parameters Impact Tumoricidal Durability and Cell Death Pathways in a 3D Ovarian Cancer Model

Abstract: The successful implementation of photodynamic therapy (PDT)-based regimens depends on an improved understanding of the dosimetric and biological factors that govern therapeutic variability. Here, the kinetics of tumor destruction and regrowth are characterized by systematically varying benzoporphyrin derivative (BPD)-light combinations to achieve fixed PDT doses (M × J/cm2). Three endpoints were used to evaluate treatment response: 1.) Viability evaluated every 24 hours for 5 days post-PDT; 2.) Photobleaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 133 publications
(415 reference statements)
2
61
2
1
Order By: Relevance
“…Previous studies from our group have demonstrated that BPD-PDT significantly decreases the size of 3-D OvCa nodules 20 and synergistically enhances carboplatin efficacy. 21 These and other studies 31,59,61,68 suggest a role for 3-D models in improved treatment planning, including for PDT regimens. The myriad of variables that influence PDT outcomes, including the marginal benefit gained from dose escalation, PS concentration, fluence, and the metrics used to evaluate treatment response require further optimization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from our group have demonstrated that BPD-PDT significantly decreases the size of 3-D OvCa nodules 20 and synergistically enhances carboplatin efficacy. 21 These and other studies 31,59,61,68 suggest a role for 3-D models in improved treatment planning, including for PDT regimens. The myriad of variables that influence PDT outcomes, including the marginal benefit gained from dose escalation, PS concentration, fluence, and the metrics used to evaluate treatment response require further optimization.…”
Section: Introductionmentioning
confidence: 99%
“…The myriad of variables that influence PDT outcomes, including the marginal benefit gained from dose escalation, PS concentration, fluence, and the metrics used to evaluate treatment response require further optimization. 59 Furthermore, many efforts have been made to standardize treatment response criteria, most notably by the World Health Organization (WHO), the RECIST group, and recently in a study by Wolchok et al 1,4,69 These treatment response criteria have been regularly revised to account for important effects of newer modalities in order to avoid exclusion of otherwise promising regimens from the translational research pipeline. 1,3,70 These concepts related to critical evaluation of treatment response metrics can be translated to HTS platforms as bioengineered 3-D tumor models become increasingly sophisticated and could complement current treatment planning approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in the literature have investigated the effect of PDT on ovarian and pancreatic cancer in a variety of models including cell lines [61], 3D cell culture [62][63][64], transplanted mice [65,66] and Phase I/II human trials [67,68]. A benzoporphyrin derivative (BPD) at 0.25 μM was able to reduce cell viability and volume in the human ovarian carcinoma cell line OVCAR5 and penetrate well through OVCAR5 3D cell culture [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…A benzoporphyrin derivative (BPD) at 0.25 μM was able to reduce cell viability and volume in the human ovarian carcinoma cell line OVCAR5 and penetrate well through OVCAR5 3D cell culture [62,63]. In another study in which OVCAR5 cells were grown in a culture film a fibre optic delivery system was used where the PS (pheophorbide) and oxygen gas was delivered separately [64].…”
Section: Discussionmentioning
confidence: 99%